2014
DOI: 10.1038/bmt.2013.217
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of infectious complications by the combination of plasma procalcitonin level and localized infection before allogeneic hematopoietic cell transplantation

Abstract: We previously reported that the baseline C-reactive protein level did not predict infectious events after hematopoietic cell transplantation (HCT). Procalcitonin (PCT) has recently emerged as a powerful biomarker for the early diagnosis of bacterial infection. We evaluated the ability of the baseline PCT level to predict early infectious events after HCT in 79 recipients who received HCT between 2008 and 2012. The high-PCT group (X0.07 ng/mL, n ¼ 27) frequently experienced documented infection (DI) (21.2% vs 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…22 Post-transplant infection included microbiologically documented infections and presumed infections based on clinical and/or radiological findings. 23 Febrile neutropenia was excluded if any other noninfectious etiology was highly suspected. Engraftment failure was defined as failure to achieve an ANC of 500/mm 3 by day 28 after transplantation.…”
Section: Study Subjectsmentioning
confidence: 99%
“…22 Post-transplant infection included microbiologically documented infections and presumed infections based on clinical and/or radiological findings. 23 Febrile neutropenia was excluded if any other noninfectious etiology was highly suspected. Engraftment failure was defined as failure to achieve an ANC of 500/mm 3 by day 28 after transplantation.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Sato et al reported that a relatively high serum CRP level before the first consolidation chemotherapy was predictive of infectious events after the initial chemotherapy had reduced the interference effect of tumor cells on CRP levels, the area under the ROC curve (AUC) was 0.67 [22]. In patients with allogeneic hematopoietic cell transplantation, two studies reported a significantly greater number of infections in the high-CRP quartile compared to the low-CRP group [20,21], but other studies found that baseline CRP levels were not independently significantly predictive of infectious events [23,24], possibly due to an insufficient sample size or the effect of prophylactic antibiotics. The results of this study in a large population reinforce the connection, the CRP levels pre-LT were independently associated with 30-day CSI post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Fever was defined as an axillary body temperature of 37.5 ° C or more according to the diagnostic criteria for febrile neutropenia. Except for bloodstream infections (BSIs), documented infections DIs were defined as microbiologically documented or presumed infections based on clinical and/or radiological findings 7 . BSIs were analyzed independently from general “ documented infection ” in this study.…”
Section: Methodsmentioning
confidence: 99%